The Ark of Nuh (AS) - "Khan, Saniyasnain" (China; Goodword book, 2024)
This enchantingly illustrated board book delightfully introduces children to the inspiring story of Prophet Nuh (Noah). Using simple and engaging language, the book shares his unwavering faith, patience, and dedication to spreading Allah$1 (Bs message. The story highlights important values such as perseverance, trust in Allah, and compassion for all creatures. Each page is brought to life with bright, colorful illustrations that captivate young imaginations. Designed for toddlers and preschoolers, the sturdy board book format is perfect for little hands and repeated reading. This book offers a meaningful way for families to nurture early spiritual growth and appreciation for the lessons of Prophet Nuh$1 (Bs life.s
Keywords: Prophets Stories